Estimating the Biological Variables of Thyroid Patients and Their Impact on Diabetics in Kirkuk - Hassan, Sara Sami; Zainal, Israa Ghassan (South Eastern European Journal of Public Health, 2024)
Background: Investigating the impact of sugar on biochemical variables in patients with thyroid dysfunction in Kirkuk, including some previously unmeasured biological variables. Materials and Techniques: From November to May, this study occurred in Kirkuk. Blood samples were collected from 120 patients aged 20 to 80 years, including 40 diabetics, 40 with both hyperthyroidism and diabetes, and 40 with both hypothyroidism and diabetes, as well as 40 healthy individuals aged 20 to 40 without chronic diseases. Levels of TSH, T4, T3, HbA1c, GPT, GOT, ALP, and HBs were measured in the serum using Beckman Coulter Access2, Spectrophotometer, and Boditech Med INC I-Chroma AFP-25 devices. Results: The study found that TSH levels were significantly elevated in patients with diabetes and hypothyroidism (P≤0.01), while T4 and T3 levels were significantly decreased (P≥0.01). HbA1c levels showed a significant increase (P≤0.01) in all groups: diabetes with hypothyroidism, diabetes with hyperthyroidism, and diabetes alone. Enzyme levels (GOT, GPT, ALP, HBs) were also significantly elevated (P≤0.01) in these groups. Conclusion: In conclusion, TSH regulation is vital, with high levels indicating hypothyroidism related to obesity and diabetes. Elevated HbA1c shows poor glucose control, and hyperthyroidism with diabetes worsens liver function and glucose metabolism, stressing the need for integrated management.